REVAMPING GOVERNMENT ACCOUNTING: IMPACT OF NEW SYSTEMS ON FINANCIAL GOVERNANCE - Clarke, Simon (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
The new governmental accounting system introduces a distinct division, encompassing the management system of basic principles and the accounting management system of accounting disciplines and tables. Unlike the traditional accounting system, this innovative approach separates these two accounting domains, marking a significant shift towards integrating financial and budget accounting methods. This division brings about a transformation in both accounting and management practices, offering unique insights into government financial operations.